Iqbal and Muslim Unity - Sanusi bin Junid, Sanusi bin (Intellectual Discourse, 2013)
This paper examines the views of Mohd. Iqbal concerning Muslims and analyzes his ideas to attain Muslim unity. Iqbal, known as the poet philosopher of Pakistan, was not a narrow nationalist and his vision was not limited to Pakistan. Iqbal's vision was ummatic and hence he should be referred to as "the poet philosopher of Muslim unity." He had a distinct conception of Muslim unity and suggested clear cut guidelines to attain that cherished goal. These ideas were as much relevant to his times as they are relevant to the contemporary Muslim world which is characterized by disunity.